Comparative genomics and community curation further improve gene annotations in the nematode Pristionchus pacificus - Athanasouli, Marina; Witte, Hanh; Weiler, Christian; Loschko, Tobias; Eberhardt, Gabi; Sommer, Ralf J.; Rödelsperger, Christian (BMC genomics, 2020)
Nematode model organisms such as Caenorhabditis elegans and Pristionchus pacificus are powerful systems for studying the evolution of gene function at a mechanistic level. However, the identification of P. pacificus orthologs of candidate genes known from C. elegans is complicated by the discrepancy in the quality of gene annotations, a common problem in nematode and invertebrate genomics. Here, we combine comparative genomic screens for suspicious gene models with community-based curation to further improve the quality of gene annotations in P. pacificus. We extend previous curations of one-to-one orthologs to larger gene families and also orphan genes. Cross-species comparisons of protein lengths, screens for atypical domain combinations and species-specific orphan genes resulted in 4311 candidate genes that were subject to community-based curation. Corrections for 2946 gene models were implemented in a new version of the P. pacificus gene annotations. The new set of gene annotations contains 28,896 genes and has a single copy ortholog completeness level of 97.6%. Our work demonstrates the effectiveness of comparative genomic screens to identify suspicious gene models and the scalability of community-based approaches to improve the quality of thousands of gene models. Similar community-based approaches can help to improve the quality of gene annotations in other invertebrate species, including parasitic nematodes.